(untitled) (Emancipação, 2021)
This theoretical essay aims to address the power of individual choice of the actors that make up the dynamics of buying and selling food, with the aim of guiding the idea that it cannot be seen as mere merchandise and reduced to marketing processes. In the view exposed here, both food should not be identified as a purely commercial object, as the existing relations in the production and acquisition of these permeate and are directly linked to the choices, be they of what, how and where to produce, or what and from where consume. To this end, a bibliographic research was carried out that directs the validation of these aspects, points out possible paths for commercialization and as a real alternative characterizes them as countermovements. Actions that permeate today’s society signal a new social order of consumption which, within capitalism itself, considers individual choice. The essay instigates the individual, to think that their actions are not merely linked to mass knowledge, and that local and cultural relations make up new attitudes and choices and these are capable of modifying the social context.